Future directions in feedback on second language writing: Overview and research agenda - Hyland, Fiona (International Journal of English Studies, 2010)
This article provides an overview of the contributions made to this special issue on feedback by the seven papers, examining how they reflect both the growing interest in different areas of research into feedback on writing and the continuing search by teachers for more effective feedback practices. Focusing first on the papers by Van Beuningen, Storch, Evans, Hartshorn and Allen, it discusses how these papers situate written corrective feedback research in the wider area of second language acquisition research and contribute to the debate in feedback research on research design issues. This is followed by an examination of the major findings of the four situated empirical studies by Bitchener, Ma, El-ebyary and Windeatt, and Martinez and Roca, which make up the second section. Echoing the authors of these papers, this article argues that we need more longitudinal naturalistic studies, adopting both cognitive and socio-cultural SLA frameworks to investigate the role of feedback and its impact on individual learners in more depth. Finally some pedagogic implications are discussed, including the need for feedback practices which facilitate students’ abilities to self regulate and evaluate their performance, and the need to raise teachers’ awareness of the different feedback sources and modes of delivery available to them.